2019
DOI: 10.1371/journal.pone.0224727
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological significance of Thrombospondin-4 expression in the tumor microenvironment of gastric cancer

Abstract: IntroductionThrombospondin-4 [1] is an extracellular glycoprotein involved in wound healing and tissue remodeling. Although THBS4 is reportedly frequently expressed in solid tumors, there are few reports of the clinicopathological features of carcinomas with THBS4 expression. We evaluated the clinicopathologic significance of THBS4 expression in gastric carcinoma (GC).Materials and methodsWe retrospectively analyzed the cases of 584 GC patients. The expression of THBS4 in each tumor was evaluated by immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
(28 reference statements)
2
22
0
Order By: Relevance
“…Heat maps in Oncomine presented that the color in the diffuse type was darker than the intestinal type, in accordance with the previous study (Förster et al, 2011). Kuroda et al showed that it was cancer-associated fibroblasts (CAFs) rather than normal-associated fibroblasts that expressed THBS4, and high expression of THBS4 was correlated with larger tumor size, more aggressiveness, lymph node metastasis, and poor OS, which was similar to our findings (Kuroda et al, 2019). Research studying the mechanism of THBS4 in GC is rare, and in endothelial cells, TGF-β1 can upregulate the THBS4 expression and affect angiogenesis, contributing to tumor growth (Muppala et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Heat maps in Oncomine presented that the color in the diffuse type was darker than the intestinal type, in accordance with the previous study (Förster et al, 2011). Kuroda et al showed that it was cancer-associated fibroblasts (CAFs) rather than normal-associated fibroblasts that expressed THBS4, and high expression of THBS4 was correlated with larger tumor size, more aggressiveness, lymph node metastasis, and poor OS, which was similar to our findings (Kuroda et al, 2019). Research studying the mechanism of THBS4 in GC is rare, and in endothelial cells, TGF-β1 can upregulate the THBS4 expression and affect angiogenesis, contributing to tumor growth (Muppala et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Thrombospondin-4, a cell-cell and cell-matrix interaction promoting protein, was found to be expressed within stromal cells absent of cytokeratin expression, which correlated with higher invasion, metastasis, and worse overall outcome clinically [103]. IL-6, a pro-inflammatory cytokine that is excreted in the CAFs via tumor stroma, progresses gastric cancer through JAK2/STAT3 signaling pathway, enhances epithelial-to-mesenchymal transition (EMT) and migration of gastric cancer cells [104]. Lactic acid, a secondary metabolite found as a byproduct of the Warburg effect, has been shown to promote macrophage polarization through angiogenic signaling via HIF1a and is highly prominent within the gastric cancer microenvironment [105].…”
Section: Cancer-associated Fibroblasts and Immune Modulationmentioning
confidence: 99%
“…The stroma-rich subtype, had the highest level of stroma signature score. Genes known to be associated with stromal content and cancer-associated fibroblasts (THBS4, CNTN1, CXCL14 and BOC) [77][78][79][80] were differentially expressed (Fig. 5).…”
Section: Figure 5 -Genomic and Transcriptomic Characteristics Of Patients With Metastatic Urothelial Carcinoma Stratified By Mrna Subtypementioning
confidence: 99%